2013
DOI: 10.1080/13546783.2013.865000
|View full text |Cite
|
Sign up to set email alerts
|

The role of analytic thinking in moral judgements and values

Abstract: While individual differences in the willingness and ability to engage analytic processing have long informed research in reasoning and decision making, the implications of such differences have not yet had a strong influence in other domains of psychological research. We claim that analytic thinking is not limited to problems that have a normative basis and, as an extension of this, predict that individual differences in analytic thinking will be influential in determining beliefs and values. Along with assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 83 publications
12
133
0
2
Order By: Relevance
“…Paxton, Unger, and Greene (2012) showed that priming analytic thinking increases utilitarian moral judgments. In a similar vein, a more recent study suggested that analytic thinking can be a factor in determining disgust-based moral judgments (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014). That is, individual differences in analytic thinking predict variation in judgments of wrongness about conventionally immoral acts: People who have a tendency to think more analytically are less likely to find disgusting acts immoral.…”
Section: Discussionmentioning
confidence: 93%
“…Paxton, Unger, and Greene (2012) showed that priming analytic thinking increases utilitarian moral judgments. In a similar vein, a more recent study suggested that analytic thinking can be a factor in determining disgust-based moral judgments (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014). That is, individual differences in analytic thinking predict variation in judgments of wrongness about conventionally immoral acts: People who have a tendency to think more analytically are less likely to find disgusting acts immoral.…”
Section: Discussionmentioning
confidence: 93%
“…Stanovich (e.g., 2004;2009b) has argued that thinking disposition is an underappreciated determinant of psychological outcomes. Recent research has supported the idea that cognitive style plays a consequential role in psychological domains that are of some general import (Pennycook, Fugelsang, & Koehler, 2015b): e.g., creativity (Barr, Pennycook, Stolz, & Fugelsang, 2014), moral judgments and values (Paxton, Unger, & Greene, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014b;Rozyman, Landy, & Goodwin, 2014), religious belief (Gervais & Norenzayan, 2012;Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2016;Shenhav, Rand, & Greene, 2012), bullshit receptivity (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2015), and even Smartphone technology use (Barr, Pennycook, Stolz, & Fugelsang, 2015 …”
Section: Individual Differences In Analytic Thinkingmentioning
confidence: 99%
“…There are may ways to "believe in God", some of which may be impervious to any sort of reflection. Cognitive reflection differentially predicts different facets of religiosity (Bahçekapili & Yilmaz, 2017), as well as religious affiliation (Pennycook et al, 2012) and other related constructs (Pennycook, Cheyne, Barr, Koehler & Fugelsang, 2014b;Saribay & Yilmaz, 2017;Yilmaz & Saribay, 2016). And other measures of reflection, as well as CRT items, predict specific religious beliefs such as endorsement of "divine command theory " Piazza & Landy, 2013;Baron et al, 2015), a view that explicitly discourages reflection on the ground that the word of God is beyond human understanding.…”
Section: Future Questions and Constraints On Generalitymentioning
confidence: 99%